Design of a Web-Based Information System for Family Card and ID Card Referral Letter Services in Banyuadem Village - Rahma Angga (oneamrd (One a Mllions Dreams Corporation), 2026)
Population administration services, such as the issuance of Family Cards (KK) and Resident Identity Cards (KTP), are vital elements of village-level governance. However, at the Banyuadem Village Office, the process for requesting introductory letters is still handled manually. Residents are required to visit the hamlet head's home in person to obtain the letter, bring the necessary documents to the village office, and write their application on a sheet of paper, which is then manually recorded by staff in a ledger. This procedure results in lengthy service times and disorganized document management. This research aims to develop a web-based information system for processing KK and KTP introductory letter requests to improve time efficiency for residents and facilitate data management for village staff. The system is designed using the PHP (Hypertext Preprocessor) programming language and MySQL as the database server. The outcome of this research is a web-based platform that allows residents to submit applications without physically visiting the village office, while also enabling the village secretary to easily store data in the database and automatically generate monthly reports